Learning Model Reading Arabic Alphabet (Al-Qur'ān) with An-Nahḍiyah Method in Elementary Grade - M. Syahrul Munir (Prodi Bahasa Arab dan Lembaga Bahasa Institut Pesantren KH Abdul Chalim Mojokerto, 2020)
Purpose - The purpose of this study is to understand the process and constraints of using the method an-nahḍiyah in teaching reading the Koran - basic Arabic language - through online books. Design/methodology/approach - Because this research focuses on uncovering the learning process with a particular method, the design chosen is qualitative with direct observation to find out the process of applying the method and interviews with several instructors related to the constraints experienced. Findings - The findings of this study, that teaching with the method an-nahḍiyah through online books there are two stages carried out, namely guided learning with teachers and independent. Furthermore, because this teaching is in an-nahḍiyah, the teacher must be able to ensure the learning objectives are achieved. Originality/value – The benefit of this research is that teaching at an- nahḍiyah is not as easy as the level afterward, and the teacher must realize that at this level teaching must follow and according to the convenience of students, not vice versa students must follow any method applied by a teacher. Paper type – Concept Paper